How to win any argument : without raising your voice, losing your cool, or coming to blows - Mayer, Robert, 1939 July 27- (Career Press, 2005)
Are you the parent of an argumentative teen or a teen with an argumentative parent? Are you anticipating an argument with your boss when you ask for a raise? Are you expecting trouble from a supplier, contractor, landlord, or subordinate? Or do you just ignore conflict situations hoping that they'll magically disappear or solve themselves? The art of argument. It's mysterious and powerful. It's the art of having things go your way. But also it's the art of getting out of your own way. It's having The Moves. But it's also about having The Touch. Arguing. There's the rough and tumble of the norm, the amateur's game. Then there's the pro's game--always knowing what to say, how to say it, and when to say it. Winning arguments without quarreling, squabbling, tussling, wrangling, bickering, raising your voice, losing your cool, or coming to blows. Winning arguments without bulldozing and browbeating the other guy. Winning arguments by finessing rather than forcing, kickin' butt or being in the other guy's face. Winning arguments without offending or embarrassing anyone, including yourself. Winning arguments with confidence, grace and ease. The New York Times described Bob Mayer's winning methodology as " ... martial. It's mental judo. Where you use the other guy's energy to win. It's mind-set. It's charisma ... a non-threatening approach that in many ways builds on the principles laid out long ago in Dale Carnegie's How to Win Friends & Influence People." So find yourself a comfortable chair. Pour yourself a cup of coffee. Sit back, relax. By the way, don't go looking for charts, graphs, or boring stats. You won't find any psychobabble here. Mayer drives home his eye-opening lessons in a light, humorous, page-turning read filled with personal and celebrity anecdotes and riveting tidbits. Talk show host Larry King calls Bob "a lawyer's lawyer." Robert Mayer conducts negotiation, mediation, and persuasion seminars and workshops for M.B.A. students, lawyers and law school students, professional associations and businesses